Вплив умов та тривалості зберігання на швидкість втрат блиску ягід суниці - Заморська, Ірина Леонідівна (НТУ "ХПІ", 2018)
Досліджено ступінь блиску поверхні та втрати маси ягід суниці сорту Хоней залежно від умов зберігання: без охолодження (за температури 20 ±1 °С та відносної вологості повітря 55-60 %) та з охолодженням (за температури 0±1 °С та відносної вологості повітря 90-95 %). Встановлено, що поверхня ягід суниці під час зберігання в різних умовах поступово втрачає блиск і через декілька годин від початку зберігання стає повністю тьмяною. Доведено, що за умов зберігання ягід суниці без охолодження втрата ознак свіжості починається вже через 1 год за досягнення втрат маси 2,5 %, тоді як в умовах холодильника - через 2 год, з рівнем втрат маси 2,0 %.

The purpose of the work is to study the effect of storage conditions and duration of Honey strawberry on the fastness of strawberry shine change. The degree of surface shine and mass losses of Honey strawberry depending on storage conditions were studied: without cooling (at temperature 20 ±1 °С and air relative humidity 55-60 %) and with cooling (at temperature 0±1 °С and air relative humidity 90–95 %). During the research, natural mass losses were measured by weighing fixed samples and the degree of strawberry shine - visually by a 5-point scale, where 1 - dim berry surface, without shine, and 5 - shiny glossy surface. It has been found out that during the storage in different conditions strawberry surface gradually loses its shine and some hours later, from the beginning of storage, it becomes completely dim. When stored without cooling at room temperature and air relative humidity the degree of strawberry surface shine decreases rapidly. An hour later strawberry surface gets dim in these conditions, which corresponds to mass loss at level of 2,5 %, and after 2,5 hours from the beginning of the trial strawberry surface loses its shine completely. Natural mass losses of strawberries are 4,6 %. Strawberries maintained shiny glossy surface within an hour and a half (1,5 hour) in the conditions of refrigerated storage. Strawberry surface began to dim after 2 hours; their mass loss was 2,0 %. The studies proved a strong inverse correlation between the degree of strawberry shine and mass losses in different storage conditions: for storage conditions without cooling (r=-0,91), for refrigerated storage (r=-0,94). It has been confirmed that when strawberries are stored without cooling the loss of freshness begins after 1 hour and mass loss is 2,5 %, whereas in refrigerated storage it occurs after 2 hours and mass loss is 2 %.
The effect of storage conditions and duration on the speed of strawberry shine loss
Keywords: втрати маси; температура; сорт Хоней; охолодження; weight loss; temperature